2002
DOI: 10.1111/j.1741-3737.2002.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Factors Influencing Maternal Stress During the First Three Years

Abstract: ࡗ Multilevel Factors Influencing Maternal Stress During the First Three YearsThis prospective study applies family stress theory to the influence of personal, child, and familial factors on a mother's parenting stress during the first 3 years of her infant's life. Participants included 134 mothers and their infants at ages 1, 6, 15, 24, and 36 months from one site of a multisite, longitudinal study. Mother's personality was most predictive of parenting stress cross-sectionally and longitudinally. Intimacy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
138
2
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 39 publications
13
138
2
11
Order By: Relevance
“…Neuroticism, which is an individual's tendency to experience negative affect and to perceive the world as distressing and threatening, was related to feelings of insufficiency as a parent and inability to meet the challenges of child-rearing. Conversely, high extraversion in assertive and active individuals, who tend to experience positive emotions, predicted lower levels of parenting stress.These findings were in line with Hypothesis 1 and also supported the results of many previous studies (e.g., de Haan et al, 2009;Mulsow et al, 2002). They were also in line with prior 21 studies that have underscored the key role of neuroticism and extraversion-the Big Two-in parenting (e.g., Metsäpelto & Pulkkinen, 2003) and in well-being among adults in general (Kokko, Tolvanen, & Pulkkinen, 2013).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Neuroticism, which is an individual's tendency to experience negative affect and to perceive the world as distressing and threatening, was related to feelings of insufficiency as a parent and inability to meet the challenges of child-rearing. Conversely, high extraversion in assertive and active individuals, who tend to experience positive emotions, predicted lower levels of parenting stress.These findings were in line with Hypothesis 1 and also supported the results of many previous studies (e.g., de Haan et al, 2009;Mulsow et al, 2002). They were also in line with prior 21 studies that have underscored the key role of neuroticism and extraversion-the Big Two-in parenting (e.g., Metsäpelto & Pulkkinen, 2003) and in well-being among adults in general (Kokko, Tolvanen, & Pulkkinen, 2013).…”
supporting
confidence: 82%
“…For instance, Mulsow, Caldera, Pursley, Reifman, and Huston (2002) showed that an aggregate score of high extraversion, agreeableness, and emotional stability was associated with lower levels of parenting stress in mothers of newborns and decreased the odds of them being chronically distressed after two years. In another study, de Haan et al (2009) showed that mothers and fathers with high extraversion and agreeableness perceived themselves as being competent enough to handle difficulties with their school-going children, to cope with the daily demands of parenting, and to exercise control over their children's misbehaviors six years later, all of which in turn was reflected positively in their parenting behaviors.…”
Section: Reciprocal Associations Between Personality Traits and Parenmentioning
confidence: 99%
“…사회생활에서 자신에게 맡겨진 일에 대한 성공적인 경험들은 자신의 능력에 대한 믿음을 긍정적으로 예측하며, 가정 내 자신의 역할도 성공적으로 수행해낼 수 있을 것이라는 믿음을 갖 게 하여 가정 내 역할에도 긍정적인 영향을 미치는 것으로 나타난다 (서주현, 김진경, 2012;안지 영, 2003;허혜경, 김민정, 2012;Kuhn & Carter, 2006). 뿐만 아니라 자신을 사랑하고 가치 있는 사람으로 지각하도록 도와 개인의 삶의 질을 향상시 킨다고 알려진 자아존중감 역시 양육스트레스와 부부간의 원만한 관계에 영향을 미치는 것으로 확인된다 (정주영, 2013;Mulsow, Caldera, Pursley, Reifman, & Huston, 2002). 자기일치이론에 따 르면 높은 자아존중감을 가진 사람은 적절하고 만족감을 유발하는 자기이미지(self-image)를 가 지고, 낮은 자아존중감을 가진 사람은 계속된 실패로 인해 만족을 유발할 수 없는 부적절한 자 기이미지를 가지게 된다 (Judge & Bono, 2001;Korman, 1970).…”
unclassified
“…자기일치이론에 따 르면 높은 자아존중감을 가진 사람은 적절하고 만족감을 유발하는 자기이미지(self-image)를 가 지고, 낮은 자아존중감을 가진 사람은 계속된 실패로 인해 만족을 유발할 수 없는 부적절한 자 기이미지를 가지게 된다 (Judge & Bono, 2001;Korman, 1970). 관련 선행연구들 (Judge & Bono, 2001;Mulsow et al, 2002) 역시 자아존중감이 높을수록 양육에 대한 어머니의 스트레스가 낮아 지며 (Kuster, Orth, & Meier, 2013) 친사회적인 행동을 가질 마음의 여유를 갖게 함으로써 부부 간의 관계에도 긍정적인 영향을 미칠 수 있음을 보고한다 (신동주, 최현미, 2011). 이러한 자아존 중감은 자신이 속한 환경에서의 유능감 지각에 많은 영향을 받는데 (Kuster et al, 2013) 2) 심리적 특성: 자기효능감, 자기존중감, 우울 어머니의 자기효능감은 Pearlin, Lieberman, Menaghan과 Mullan(1981) (Anderson & Gerbing, 1988 (Hu & Bentler, 1999).…”
unclassified
“…(12) tyrimai rodo, kad neigiama emocinė patirtis, globojant vaiką, yra susijusi su nejautriu ir nepalankiu motinų elgesiu. Daugelis tyrimų patvirtinta, kad motinos, auginančios sutrikusios raidos vaikus, patiria didesnį stresą (18)(19)(20)(21)(22)(23)(24). Sutrikusios raidos diagnozė tėvams gali sukelti įvairių emocinių reakcijų: didesnis psichologinis skausmas (gėdos, bejėgiškumo, beviltiškumo ir kt.…”
unclassified